How to write for animation. - Scott, Jeffrey, ....- (Woodstock : Overlook, 2002)
Recent years have seen a boom in animation-an expanding market that is luring writers who have an eye toward the future and an eagerness to work in a medium where the only limit is the depth of one's imagination. Award-winning animation writer Jeffrey Scott details the process of developing even the vaguest of ideas into a fully realized animation script. How to Write for Animation is the ultimate guide for anyone with ambitions of writing for the most rapidly developing medium in all of entertainment.